Amelioration of acid sulphate soils in Nilwala river basin : Amelioration of acid sulphate soils (SAARC Journal of Agriculture, 2022)
Paddy tracts of Nilwala basin has been affected by the implementation of Nilwala Flood Protection and Drainage Project in 1979 due to excessive drainage, and nearly 7000 acres of land is abandoned. The water table goes down to the level of 50 cm below soil surface during dry periods and soil pH falls to 3-4 causing acid sulphate condition. Hitherto several efforts have been made to ameliorate the paddy lands but no any economical solution is obtained. The National Science Foundation project to find out the feasibility of using natural hydraulic forces to increase water table to keep the acid sulphate forming minerals at bay and to cultivate rice in these paddy lands. Water table fluctuation in relation to water level in the drainage channel was studied over one year and there was found a very high correlation (r2=0.985) indicating a possibility of increasing water table by heading up water in the channel. Simulated pot experiment showed that increasing water table to 15 cm below soil surface allows rice to grow effectively, showing plant survival of 112 (53%) compared to 28 (15%) plants in control. Recorded plant height of Bg. 357 variety was 35 cm compared to 22 cm in different treatments and control, respectively. Soil pH also increased to a value closer to 6.0 in the treatment which is conducive for rice cultivation. However, the low values of plant survival and plant heights were due to unusual extreme low rainfall in 2020/21 Maha season compared to 10 years’ average.SAARC J. Agric., 20(2): 211-221 (2022)